PENANGANAN TUNGGAKAN DANA BERGULIR (NON PERFORMING LOAN) PASKA PELAKSANAAN PNPM MANDIRI PEDESAAN - Siti Nuraini (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2016)
The purpose of this research to looking for handling problems after the implementation of PNPM Mandiri Rural especially for arrears (non performing loan) revolving funds that has become asset the community. For the first time, monitoring and evaluation originally carried out by the external but after the program is will be by the community.This research used methodology qualitative to technique observation, interviews and focuss group discussion (FGD).This result indicates that the development of asset revolving funds activity management units (UPK) is 56 %.Arrears revolving funds accidents was at the beginning of the program because the weak of institutional and monitoring to the beneficiaries.Handling arrears (non performing loan ) should be conducted in a family spirit have not yet decided to the police.This advice especially to the local government is to supervision and strengthening institutional owned by the activity management units (UPK) because revolving funds managed quite large and gave benefits received by the public is also quite a lot Keyword : Activity management units (UPK), arrears, revolving funds